2020
DOI: 10.3389/fphar.2020.00320
|View full text |Cite
|
Sign up to set email alerts
|

The Apelin/APJ System in Psychosis and Neuropathy

Abstract: Apelin, an endogenous neuropeptide, has been identified as the cognate ligand for the Gprotein-coupled receptor APJ. Apelin, APJ messenger RNA, and protein are widely expressed in the central nervous system and peripheral tissues of humans and animals. The apelin/APJ system has been implicated in diverse physiological and pathological processes. The present article reviews the progress of the latest research investigating the apelin/APJ system in pain, depression, anxiety, memory, epilepsy, neuroprotection, st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…There was a significant decrease in the proportion of cells expressing both aplnr and apln in the AP of SHRs in comparison to WKY rats (24 % vs 41 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]% respectively, p<0.05). No change in the percentage co-localization of aplnr with apln was seen in the OVLT or SFO of SHRs in comparison to WKY rats (36 [29][30][31][32][33][34][35][36][37][38][39][40]% vs 31 % and 15 [12][13][14][15][16][17][18][19][20]% vs 20 [17][18][19][20][21][22][23][24][25][26]% respectively, p>0.05).…”
Section: Co-localization Of Aplnr and Apln In Normotensive And Shr Cvosmentioning
confidence: 78%
See 1 more Smart Citation
“…There was a significant decrease in the proportion of cells expressing both aplnr and apln in the AP of SHRs in comparison to WKY rats (24 % vs 41 [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]% respectively, p<0.05). No change in the percentage co-localization of aplnr with apln was seen in the OVLT or SFO of SHRs in comparison to WKY rats (36 [29][30][31][32][33][34][35][36][37][38][39][40]% vs 31 % and 15 [12][13][14][15][16][17][18][19][20]% vs 20 [17][18][19][20][21][22][23][24][25][26]% respectively, p>0.05).…”
Section: Co-localization Of Aplnr and Apln In Normotensive And Shr Cvosmentioning
confidence: 78%
“…hypothalamic supraoptic (SON) and paraventricular (PVN) nuclei) and lower brainstem structures (e.g. nucleus of the solitary tract (NTS), area postrema (AP)) [7], thus allowing for multiple roles in the central regulation of physiological systems such as cardiovascular control [8,9], angiogenesis [10], autonomic signalling [11][12][13], neuroprotection [14], fluid homeostasis [15], and modulation of hypothalamic-pituitary-adrenal axis activity [16,17]. In some brain structures, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The APLN/APLNR pathway may also serve as a promising therapeutic target for the treatment of psychosis and neuropathy (Lv et al, 2020). We further investigated the influence of APLN/APLNR pathway polymorphisms on the risks of depression and anxiety in patients with CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The APLN/APLNR signaling pathway is involved in various pathological processes and physiological functions, including cardiovascular disease, angiogenesis, energy metabolism, and central nervous system disease (Lv et al, 2020). A previous meta-analysis has shown that the circulating apelin level is a prominent athero-protective marker against the development of CAD, while the APLNR rs9943582 polymorphism in the APLNR promoter, is associated with an increased risk of CAD (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The apelin/APJ system is involved in a broad range of physiological functions and pathological processes, including cardiovascular function ( Wysocka et al, 2018 ; Esmaeili et al, 2019 ), cardiac contractility ( Zhong et al, 2017 ; Esmaeili et al, 2019 ), angiogenesis ( Wu et al, 2017 ; Cheng et al, 2019 ), energy metabolism ( Bertrand et al, 2015 ; Castan-Laurell et al, 2019 ), liver diseases ( Principe et al, 2008 ; Lv et al, 2017 ), ischemia/reperfusion injury ( Yang et al, 2015 ; Chen et al, 2016 ) and cancer ( Yang et al, 2016a ; Masoumi et al, 2020 ). Recent studies were focused on the role of apelin in psychosis and neuropathy ( Lv et al, 2020 ). Xiao et al (2018) demonstrated that intrahippocampal infusion of apelin-13 (1-4 Ī¼g/rat) exhibited an anti-depressive effect in forced swim test.…”
Section: Introductionmentioning
confidence: 99%